2020
DOI: 10.1002/jhbp.807
|View full text |Cite
|
Sign up to set email alerts
|

Acute and subacute effects of irreversible electroporation on normal common bile ducts in a rabbit model

Abstract: BACKGROUND Malignant biliary tumors are uncommon and usually diagnosed following malignant biliary obstruction. 1 Surgical resection is currently the only potential curative treatment for early recognition and diagnosis. However, a majority of patients present late in the course of disease with only 20%-40% resectable cases due to the advanced tumor stage at the time of diagnosis, and of these potentially resectable tumors, R 0 resection is not always achieved. 2 Therefore, placement of biliary stents is typic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…In this study, relatively more TI occurred in the bile duct, suggesting that the electrical energy should be controlled when applied to the bile duct. In our previous study, biliary stricture was found after exposure of the bile duct to EPs in a rabbit model, which was consistent with the findings of a clinical report ( 24 ). Biliary stricture may be associated with fibrosis in the mucosal layer, which is easily induced by heating.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, relatively more TI occurred in the bile duct, suggesting that the electrical energy should be controlled when applied to the bile duct. In our previous study, biliary stricture was found after exposure of the bile duct to EPs in a rabbit model, which was consistent with the findings of a clinical report ( 24 ). Biliary stricture may be associated with fibrosis in the mucosal layer, which is easily induced by heating.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the feasibility, safety, and efficacy of EBT for the focal treatment of cavity organs, which are usually the restricted areas of thermal-based ablation techniques, have been investigated. In our previous studies, the safety and efficacy of IRE in the stomach and bile duct have been investigated with favorable outcomes ( 21 24 ). These results demonstrate that EBT is an attractive candidate for the treatment of such endoluminal tumors.…”
Section: Introductionmentioning
confidence: 99%
“…IRE is a novel ablative technique used in the treatment of patients with LAPC that may cause cell death through apoptosis while preserving intact blood vessels and bile ducts. 23,24 Conceivably, it may represent a useful adjunct to slow down disease progression, but also for the ablation of unresectable PC, where blood vessels, bile duct, and pancreatic duct could pose a problem. Moreover, immunologic studies suggest that IRE may induce a systemic immune response that might result in the destruction of micrometastases, except from local tumor destruction, which could further improve survival.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the non-thermal features of EP, several studies have found that EP is a potential ablation method for cavity organs such as the digestive tract. The safety and e cacy of IRE for the bile duct [9,10], heart [11], and urinary tract [12] have been demonstrated in animal studies. In our previous study, the safety and e cacy of EP for gastric tissue ablation was investigated in an animal model [8].…”
Section: Introductionmentioning
confidence: 99%